Ocena zakładów ubezpieczeń działu II z uwzględnieniem preferencji odbiorcy oceny - Jędrzychowska, Anna (Analysis of Non-Life Insurance Companies, Taking Account of Preference of Estimation Receiver, 2008)
The analysis of insurance companies should improve knowledge of insurance market participant of individual insurers, as well as whole market. The article presents three different categories of recipients of analysis of insurances: - oversight actuaries, - clients, - investors. A model was built basing on financial analyses of insurance control indicators. The analysis of the non-life insurance companies operating in the Polish market between was carried out 2000 and 2004 using indicators and taxonomic method.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 112-120